Management practices in high-tech environments - Jemielniak, Dariusz; Kociatkiewicz, Jerzy (Gale virtual reference library, 2008)
Presents research on management practices in American, European, Asian and Middle-Eastern high-tech companies, with particular focus on fieldwork-driven, but reflective, contributions.